A Study To Assess The Effectiveness Of Role Play Regarding Tactile Stimulation On Good And Bad Touch Among Primary School Students At Selected School Of Surat District - Biradar, Satish; Bhagat, Vishakha; Sadiq Aliyu, Abubakar; Sohail, Salman; Muhammed, Abdullahi; Gamit, Vinita; Patel, Asma; Parmar, Riya; Gamit, Komal (Journal of Neonatal Surgery, 2025)
Introduction: Childhood is a crucial period for establishing awareness of personal safety, particularly regarding concepts of good and bad touch. Tactile stimulation and physical interactions form a significant part of children’s learning experiences; however, they can also expose them to risks if not properly understood. Aims: This study aims to assess the effectiveness of role play as an educational intervention to teach primary school students about good and bad touch. By fostering an engaging learning environment, role play has the potential to empower children with the skills needed to recognize and respond to inappropriate physical contact. This study examines whether this method can significantly improve students' knowledge, awareness, and confidence in differentiating between appropriate and inappropriate touches, ultimately contributing to their personal safety and well-being. Materials and Methods: in this study, a Quasi -experimental one group pre-test post-test design was adopted with 60 samples. An observational checklist (semi-structured questionnaire) was utilised to collect the data. The data were analysed by using descriptive and inferential statistics. Results: The study justified the impact of role play in enhancing the understanding of good touch and bad touch among primary school students where the pre-test mean score was 3.6, while the post-test mean score significantly increased to 9.55. The calculated 't' value was 24.04, which exceeds the table value of 2.000 at 59 degrees of freedom. With a significance level of 0.0001. Conclusion: The study effectively demonstrated the significant impact of role play as an intervention in improving primary school students' understanding of good touch and bad touch.